2018
DOI: 10.13189/ujer.2018.060916
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Candidates' Critical Thinking Tendencies Research in Turkey: A Content Analysis

Abstract: In this study, empirical studies related to the tendency think critically of teacher candidates in Turkey were examined. These studies were evaluated systematically by means of thematic content analysis. In research the WEB OF SCIENCES, ERIC, SCOPUS, EBSCO and ULAKBIM databases were scanned for the years 2012-2017, and 45 academic articles were examined. It was found out that studies are concentrated in the screening and relational model and work in a limited number of experimental models. Furthermore, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
2
9
0
1
Order By: Relevance
“…Among them, correlational and survey studies dominate the field, and only a few studies adopted a qualitative approach. In recent reviews of CT tendencies (Cansoy et al, 2018;İşlek & Hürsen, 2014), similar findings were reported. The international literature also supports these findings (Abrami et al, 2008;Pithers & Soden, 2000).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Among them, correlational and survey studies dominate the field, and only a few studies adopted a qualitative approach. In recent reviews of CT tendencies (Cansoy et al, 2018;İşlek & Hürsen, 2014), similar findings were reported. The international literature also supports these findings (Abrami et al, 2008;Pithers & Soden, 2000).…”
Section: Discussionsupporting
confidence: 76%
“…As the review intends to uncover common and diverging aspects across studies, it might help educators reach more solid conclusions that have implications for educational policy and practice. Also, this study differs from other review studies (e.g., Cansoy et al, 2018) in its methodology and conceptual framework. The following research questions guided our study:…”
Section: Status Of Ct In the Turkish Educational Contextmentioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, it is reported that pre-service teachers' critical thinking skills are still at the medium to low levels (Alkharusi, 2019;Cansoy et al, 2018;Sari et al, 2019). Likewise in Indonesia, some researchers report that pre-service teachers' have critical thinking dispositions (As'ari et al, 2017); and critical thinking skills are still underdeveloped (Saefi et al, 2017;Sari et al, 2019), especially in the aspect of inference (Saefi et al, 2017) and self-regulation (Nuraini, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was considered that the discussion based teaching activities, in any event, support the thinking skills. Cansoy, Parlar and Polatcan (2018) examined the research conducted on Teacher Candidates' Critical Thinking Tendencies in Turkey, they reported that the participation of individuals in discussion-based writing activities and guided group discussions develops their critical thinking tendencies.…”
mentioning
confidence: 99%